Fixation distance and fixation duration to vertical road signs. (May 2018) - Costa, Marco; Simone, Andrea; Vignali, Valeria; Lantieri, Claudio; Palena, Nicola
Abstract: The distance of first-fixation to vertical road signs was assessed in 22 participants while driving a route of 8.34 km. Fixations to road signs were recorded by a mobile eye-movement-tracking device synchronized to GPS and kinematic data. The route included 75 road signs. First-fixation distance and fixation duration distributions were positively skewed. Median distance of first-fixation was 51 m. Median fixation duration was 137 ms with a modal value of 66 ms. First-fixation distance was linearly related to speed and fixation duration. Road signs were gazed at a much closer distance than their visibility distance. In a second study a staircase procedure was used to test the presentation-time threshold that lead to a 75% accuracy in road sign identification. The threshold was 35 ms, showing that short fixations to a road signs could lead to a correct identification. Highlights: Vertical road signs are first fixated at a very close distance (mode = 35 m, median 51 m). Fixation duration increases linearly with fixation distance. Fixation distance to road signs increase linearly with speed. A presentation time of 35 ms leads to a 75% accuracy in road-sign identification.